A stretchable and self-healable organosilicon conductive nanocomposite for a reliable and sensitive strain sensor. Issue 48 (20th November 2020) - Zhang, Kaiming; Song, Chengxin; Wang, Zhe; Gao, Chuanhui; Wu, Yumin; Liu, Yuetao
Abstract : Stretchable conductive nanocomposites can be further used as strain sensors, which are extensively applied in bionic electronic devices, human activity monitoring and soft robots. Abstract : Stretchable conductive nanocomposites can be further used as strain sensors, which are extensively applied in bionic electronic devices, human activity monitoring and soft robots. However, it is a challenging task to design conductive nanocomposites with good stretching ability, high-efficiency self-healing ability and sensitive sensing ability. In this study, we skillfully compounded organosilicon networks with modified MWCNTs to prepare a kind of conductive nanocomposite elastomer. The natural small molecules, 3, 4-dihydroxybenzaldehyde (DHBA) derived from plants, were modified by the Schiff base reaction to amino poly(dimethylsiloxane) and amino-functionalized MWCNTs, respectively. The modified MWCNTs can be better dispersed in the polymer system by hydrogen bonds. Finally, zinc ions were introduced into the composite system to enhance the tensile properties. The elastomer can spontaneously achieve efficient self-healing behavior through the reversibility of hydrogen bonds, metal–ligand bonds and imine bonds. The elongation of the conductive nanocomposite containing 10 wt% modified MWCNTs was 169%, and the mechanical strength could reach 4.39 MPa. After 24 hours of repair, the tensile properties can be restored to 92.9%. In addition, the reliability and sensitivity of the nanocomposite as a strain sensor were evaluated. A high GF value of 3.7673 at 0% to 160% strain was obtained. Before and after self-healing, the elastomer has been successfully used for monitoring the subtle movements of human body (including smiling and speaking). The self-healable organosilicon conductive nanocomposites have great application potential to be a new generation of strain sensor.